PEMBERDAYAAN REMAJA PEREMPUAN TERHADAP PENTINGNYA PENDIDIKAN DI KECAMATAN BANTARAN KABUPATEN PROBOLINNGGO - Muhammad, Devy Habibi; Adawiyah, Robiatul; Agustin, Maulid; Syaifuddin Romli, Ahmad; Abadiyah, Sa’adatul (DEVELOPMENT: Journal of Community Engagement, 2023)
As women in the modern era are stakeholders of development, therefore the implementation of development must emphasize the importance of women's empowerment efforts. This article discusses a community service activity conducted to raise the awareness of adolescent girls in Legundi Village, Bantaran Sub-district, Probolinggo Regency, about the importance of education and their role in society. Through a Participatory Action Research (PAR) approach, the activity involved team preparation, observation, research and evaluation to measure the success of the activity. The evaluation results showed an increase in adolescent girls' enthusiasm for learning and understanding of the importance of education. The bibliography includes references on Islamic education, community development and character education.